(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Fitness and training for conditioning has been an important aspect of all the training programs during, before and after the competitions. Consistency of athletics performance can be ensured through systematic and scientific fitness program planning. It ensures that the athlete achieves his/her peak zone at the right time through accurate and important to consistent fitness development methods and strategies. The present study was conducted on 56 male school level athletes in the age group of 14 to 16 years who had participated at the minimum zonal level. The athletes were divided into four equal groups. Each group was subjected to 10 weeks of specifically designed circuit training. (Group-A) 5 days a week circuit training, (Group-B) 4 days a week circuit training, (Group-C) alternate day’s circuit training program was implemented to the 3 experimental groups and no any such training was imparted to the fourth that is the control group (Group-D). The 55 athletes were tested upon the two motor fitness components namely speed and agility before the intervention and later at the regular intervals of 2 weeks of the circuit training (total 6 times testing) and later all the four groups were further tested again at the 2 weeks of regular intervals without any training being implemented to them to know about the circuit training effects on their speed and agility variables. Group-A showed significant improvement in their speed component after 8 weeks of circuit training and the same group had shown significant improvement in the agility variable after 4 weeks of circuit training. In the next phase of testing without any training being imparted, group -A had shown improved performance on speed and agility component consistently over the ensuing no-training phase of 10 weeks.